Synthesis, radiolabeling, and evaluation of a (4-quinolinoyl)glycyl-2-cyanopyrrolidine analogue for fibroblast activation protein (FAP) PET imaging - Zhang, Ni; Pan, Fei; Pan, Lili; Diao, Wei; Su, Feijing; Huang, Rui; Yang, Bo; Li, Yunchun; Qi, Zhongzhi; Zhang, Wenjie; Wu, Xiaoai (Frontiers in Bioengineering and Biotechnology, 2023)
Fibroblast activation protein (FAP) is regarded as a promising target for the diagnosis and treatment of tumors as its overexpression in cancer associated fibroblasts. FAP inhibitors bearing a quinoline scaffold have been proven to show high affinity against FAP in vitro and in vivo, and have been radio-labeled for the imaging and treatment of FAP positive tumors. However, currently available FAP tracers both contain chelator groups to enable radiolabeling, making those tracers more hydrophilic and not suitable for the imaging of lesions in the brain. Herein we report the synthesis, radio-labeling, and evaluation of a 18F labeled quinoline analogue ([18F]3) as a potential FAP targeted PET tracer, which hold the potential to be blood-brain-barrier permeable. [18F]3 was obtained by one-step radio-synthesis via copper mediated SNAR reaction from corresponding boronic easter precursor. [18F]3 showed moderate lipophilicity with a log D7.4 value of 1.11. In cell experiments, [18F]3 displayed selective accumulation in A549-FAP and U87 cell lines and can be effectively blocked by the pre-treatment of cold reference standard. Biodistribution studies indicated that [18F]3 was mainly excreted by hepatic clearance and urinary excretion, and it may duo to its moderate lipophilicity. In vivo PET imaging studies indicated [18F]3 showed selective accumulation in FAP positive tumors, and the specific binding was confirmed by blocking studies. However, low brain uptake was observed in biodistribution and PET imaging studies. Although our preliminary data indicated [18F]3 hold the potential to be developed as a blood-brain-barrier penetrable FAP targeted PET tracer, its low brain uptake limits its application in detection of brain lesions. Herein we report the synthesis and evaluation of [18F]3 as a novel small molecule FAPI targeted PET tracer, and our results suggest further structural optimizations would be needed to develop BBB permeable PET tracer with this scaffold.